Ever after [videorecording (DVD)] : a Cinderella story - Tennant, Andy, 1955-; Grant, Susannah; Barrymore, Drew; Huston, Anjelica; Scott, Dougray, 1965-; Moreau, Jeanne, 1928-2017; Godfrey, Patrick; West, Timothy; Parfitt, Judy (20th Century Fox Home Entertainment, 2002)
A young woman of the 16th century stands up to her scheming stepmother and works miracles on the lives of everyone around her, including the crown prince of France.